188k views
3 votes
(2t-3)^3, can you help me?, please?

User Letroll
by
6.4k points

2 Answers

2 votes

Answer:

8t³ - 36t² + 54t - 27

Explanation:

(2t - 3)³

(2t - 3)(2t - 3)(2t - 3)

FOIL the first two binomials - first - outer - inner - last

(2t - 3)(2t - 3)

= 4t² - 6t - 6t + 9

= 4t² - 12t + 9

multiply this polynomial by the last binomial

(4t² - 12t + 9)(2t - 3)

distribute 2t

2t • 4t² = 8t³

2t • -12t = -24t²

2t • 9 = 18t

distribute -3

-3 • 4t² = -12t²

-3 • -12t = 36t

-3 • 9 = -27

combine

8t³ - 24t² + 18t - 12t² + 36t - 27

simplify

8t³ - 36t² + 54t - 27

User Riccardo Queri
by
5.5k points
4 votes

Answer:

8t^3-36t^2+54t-27

Explanation:

(2t-3)^3

(2t-3)(2t-3)(2t-3)

Multiply the first two terms

(4t^2 -6t -6t+9)(2t-3)

Combine like terms

( 4t^2 -12t +9) ( 2t-3)

Multiply

2t*( 4t^2 -12t +9) -3 ( 4t^2 -12t +9)

Distribute

8t^3 -24t^2 +18t-12t^2 +36t-27

Combine like terms

8t^3-36t^2+54t-27

User Kishieel
by
5.7k points